2019
DOI: 10.7150/jca.29397
|View full text |Cite
|
Sign up to set email alerts
|

CK7 expression associates with the location, differentiation, lymph node metastasis, and the Dukes' stage of primary colorectal cancers

Abstract: Purpose : Most colorectal cancers (CRCs) show positive immunohistochemical (IHC) staining for CK20 and negative staining for CK7. However, in clinical settings, some CRCs show positive IHC staining for CK7, and the clinicopathological significance of this needs to be studied. This study investigated the clinicopathological significance of CK7 positivity in CRCs. Materials and Methods : A total of 178 patients with CRC were used to study the clinicopathological significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 43 publications
(60 reference statements)
1
23
1
Order By: Relevance
“…Our results differ from those reported in several previous studies over the last two decades regarding anatomic distribution and prognostic significance of CK7 and CK20 expression in CRC. Zhang et al described enrichment of rectal carcinomas in terms of CK7 positivity compared to proximal colon tumors 19 , which sharply contrasts with our finding and of results published by Fei et al 25 of more frequent CK7 expression in right-sided tumors. In line with our results, Bayrak et al found that CK20 + tumors were more frequent in the left colon and rectum, and they found an association between CK20 + status and low-grade tumors.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results differ from those reported in several previous studies over the last two decades regarding anatomic distribution and prognostic significance of CK7 and CK20 expression in CRC. Zhang et al described enrichment of rectal carcinomas in terms of CK7 positivity compared to proximal colon tumors 19 , which sharply contrasts with our finding and of results published by Fei et al 25 of more frequent CK7 expression in right-sided tumors. In line with our results, Bayrak et al found that CK20 + tumors were more frequent in the left colon and rectum, and they found an association between CK20 + status and low-grade tumors.…”
Section: Discussioncontrasting
confidence: 99%
“…Concerning methodology, the best percentage cut-off points for considering CK7 + /CK7 − and CK20 + /CK20 − tumors, remains unresolved. Loupakis et al and Fei et al considered tumors with staining in > 10% of tumor cells to be positive, just as we did with CK7 13 , 25 . Al-Maghrabi considered CRCs staining in > 5% to be positive 5 .…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…GATA3 positivity, co-expression of CK7 and CK20, and CDX-2 negativity should resolve the diagnostic dilemma in doubtful cases [ 24 ]. Attention must be paid, however, to the occasional CK7 positivity of some colorectal adenocarcinomas, a finding that is a sign of dismal prognosis [ 26 ].…”
Section: Architectural Changesmentioning
confidence: 99%